\[\boxed{\mathbf{736\ (736).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[a_{1} = 4;\ \ a_{6} = - 5\]
\[a_{6} = a_{1} + 5d \Longrightarrow \ \ 5d = a_{6} -\]
\[- a_{1}\ \Longrightarrow \ d = \frac{a_{6} - a_{1}}{5} =\]
\[= \frac{- 5 - 4}{5} = - 1,8\]
\[a_{2} = 4 - 1,8 = 2,2\]
\[a_{3} = 2,2 - 1,8 = 0,4\]
\[a_{4} = 0,4 - 1,8 = - 1,4\]
\[a_{5} = - 1,4 - 1,8 = - 3,2\]
\[Ответ:2,2;\ \ 0,4;\ - 1,4;\ - 3,2.\]
\[\boxed{\mathbf{736.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ \sqrt{\frac{3}{2}},\ 1,\ \sqrt{\frac{2}{3}},\ \ldots;\ \ \ \]
\[q = 1\ :\sqrt{\frac{3}{2}} = \sqrt{\frac{2}{3}}\]
\[S = \sqrt{\frac{3}{2}}\ :\left( 1 - \sqrt{\frac{2}{3}} \right) =\]
\[= \sqrt{\frac{3}{2}}\ :\left( \frac{\sqrt{3} - \sqrt{2}}{\sqrt{3}} \right) =\]
\[= \frac{\sqrt{3} \cdot \sqrt{3}}{\sqrt{2} \cdot \left( \sqrt{3} - \sqrt{2} \right)} =\]
\[= \frac{\sqrt{3} \cdot \sqrt{2} \cdot \sqrt{3} \cdot \left( \sqrt{3} + \sqrt{2} \right)}{\sqrt{2} \cdot \sqrt{2} \cdot \left( \sqrt{3} - \sqrt{2} \right)\left( \sqrt{3} + \sqrt{2} \right)} =\]
\[= \frac{\sqrt{6} \cdot \left( 3 + \sqrt{6} \right)}{2 \cdot (3 - 2)} = \frac{3\sqrt{6} + 6}{2};\]
\[2)\ \frac{\sqrt{2} + 1}{\sqrt{2} - 1},\frac{1}{2 - \sqrt{2}},\frac{1}{2},\ldots\ \ \ \]
\[\ q = \frac{1}{2 - \sqrt{2}}\ :\frac{\sqrt{2} + 1}{\sqrt{2} - 1} =\]
\[= \frac{\sqrt{2} - 1}{\left( 2 - \sqrt{2} \right)\left( \sqrt{2} + 1 \right)} =\]
\[= \frac{1}{\sqrt{2} \cdot \left( \sqrt{2} + 1 \right)} = \frac{1}{2 + \sqrt{2}};\]
\[S = \frac{\sqrt{2} + 1}{\sqrt{2} - 1}\ :\]
\[:\left( 1 - \frac{1}{\sqrt{2} \cdot \left( \sqrt{2} + 1 \right)} \right) =\]
\[= \frac{\sqrt{2} + 1}{\sqrt{2} - 1}\ :\frac{2 + \sqrt{2} - 1}{2 + \sqrt{2}} =\]
\[= \frac{\sqrt{2} + 1}{\sqrt{2} - 1} \cdot \frac{2 + \sqrt{2}}{\sqrt{2} + 1} =\]
\[= \frac{\left( 2 + \sqrt{2} \right)\left( \sqrt{2} + 1 \right)}{\left( \sqrt{2} - 1 \right)\left( \sqrt{2} + 1 \right)} =\]
\[= \frac{2\sqrt{2} + 2 + 2 + \sqrt{2}}{2 - 1} = 4 + 3\sqrt{2}.\]